Extreme hypernatremia after a laparoscopic hysterectomy and bilateral salpingo-oophorectomy: a case report and literature review - Ding, Fei; Nie, Xin; Chen, Yuemei; Wang, Minjin; He, Yong (Frontiers in Surgery, 2024)
Congenital nephrogenic diabetes insipidus (NDI) primarily arises from an X-linked recessive inheritance caused by mutations in the AVPR2 gene, which is responsible for approximately 90% of cases. This condition has an incidence rate of 4–8 per million male live births, with females being much less frequently affected. Symptoms typically manifest shortly after birth, predominantly in males. The key clinical features of NDI include excessive urination (polyuria), compensatory excessive thirst (polydipsia), cognitive impairment, consistently low urine specific gravity, dehydration, and imbalances in electrolyte levels. This case study highlights an unusual occurrence of NDI in a 50-year-old Chinese woman attributed to a mutation in the AVPR2 gene. For more than a year, she had been suffering from excessive urination and severe thirst. The patient, who had undergone surgery for cervical cancer, developed polyuria and hypernatremia postoperatively. Initial laboratory analyses revealed normal blood sodium and chloride levels but reduced urine osmolality and specific gravity. Imaging assessments revealed no irregularities. To validate the diagnosis of NDI, she participated in a water deprivation and vasopressin test. Subsequent genetic tests revealed a thymine (T) to adenine (A) mutation, leading to a missense mutation in the AVPR2 gene. As part of her treatment, she was placed on a low-sodium diet and prescribed oral hydrochlorothiazide and indomethacin for 1 month, resulting in a marked improvement in her symptoms. To the best of our knowledge, this is the first documented case of NDI diagnosed postoperatively in an older female patient with AVPR2 heterozygosity. This case highlights an unusual instance of an X-linked recessive clinical presentation of NDI in an elderly female patient. This study also underscores the importance of conducting water deprivation, vasopressin tests, and genetic testing in establishing the underlying cause for individuals diagnosed with NDI.